Insm1, Neurod1, and Pax6 promote murine pancreatic endocrine cell development through overlapping yet distinct RNA transcription and splicing programs - Karrie D Dudek; Anna B Osipovich; Jean-Philippe Cartailler; Guoquing Gu; Mark A Magnuson (G3: Genes, Genomes, Genetics, 2021)
Abstract Insm1Neurod1Pax6Insm1Neurod1Pax6Insm1Neurod1Pax6Syt14Snap25Syt14Insm1Pax6Snap25Insm1Neurod1Pax6